1976
DOI: 10.1172/jci108513
|View full text |Cite
|
Sign up to set email alerts
|

Discoidal bilayer structure of nascent high density lipoproteins from perfused rat liver.

Abstract: A B S T R A C T Rat livers were perfused for 6 h without added plasma proteins using washed erythrocytes and buffer in a recirculating system. An inhibitor to the enzyme lecithin-cholesterol acyltransferase (5,5'-dithionitrobenzoic acid) was added in some experiments to prevent modification of substrate-lipids contained in secreted lipoproteins. The inhibitor did not detectably alter hepatic ultrastructure or gas exchange, but it inhibited the secreted lecithin-cholesterol acyltransferase by more than 85%. Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
136
1
5

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(155 citation statements)
references
References 46 publications
12
136
1
5
Order By: Relevance
“…2 b). This stacking pattern resembles that obtained from has- cent high density lipoproteins (HDL) (15). At higher concentrations the vesicles appear to fuse into multilamellar sheets (Fig.…”
Section: Resultssupporting
confidence: 63%
“…2 b). This stacking pattern resembles that obtained from has- cent high density lipoproteins (HDL) (15). At higher concentrations the vesicles appear to fuse into multilamellar sheets (Fig.…”
Section: Resultssupporting
confidence: 63%
“…The high triglyceride content of the nascent HDL that we reported earlier (3) has been confirmed. It may be related to the presence of apo B in this fraction that has also been found by Hamilton et al (19). Those investigators have shown that the apo B-containing portion of nascent HDL can be separated from the rest of this fraction by concanavalin-A affinity chromatography (20).…”
Section: Discussionsupporting
confidence: 62%
“…A similar mechanism was proposed for the accumulation of discoidal HDL in the sera of cholesterol-fed guinea pigs [6]. It is significant to note that nascent discoidal HDL with a FC:PL molar ratio of 0.65 isolated from perfused rat livers is, in contrast, a good substrate for LCAT [5]. The lipoproteins secreted into fraction 1 are spherical despite their high free cholesterol-to-phospholipid molar ratio.…”
Section: Resultsmentioning
confidence: 58%
“…De novo synthesis of discoidal HDL by perfused livers from normal and hypercholesterolemic African green monkeys was shown in [23]. The tendency of the discoidal lipoproteins to stack into rouleau formations, (fig.2b,c) is characteristic of negatively stained preparations of these abnormal lipoproteins obtained from animal [5,7] or human studies [ 1,2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation